Subtitled artefacts as communication – the case of Ocean's Eleven Scene 12. (1st November 2020) - Messerli, Thomas C.
ABSTRACT: This article examines how Ocean's Eleven 's (Soderbergh, 2001) Scene 12 and its English DVD subtitles can be analysed and understood from the perspective of the pragmatics of fiction and more generally pragmatics and communication studies. Examples from the scene are used to describe the film's participation structures. Communication with film viewers is approached from a cognitive-pragmatic perspective and in terms of Grice's Cooperative Principle. Agency in this communicative setting is discussed from the perspective of Constitutive Communication Theory. On the example of Scene 12, the article provides specific insights into the meaning of the scene in the context of the film as well as within communication between collective sender and the film's audience, and it demonstrates the usefulness of pragmatic theories for the understanding of subtitled film in general. Interlingual subtitles are instrumentalised as access points to film scenes in the first part, and they are discussed as situated language in the second part.